Experience the convenience of getting your questions answered at IDNLearn.com. Find the answers you need quickly and accurately with help from our knowledgeable and experienced experts.

Use the Principle of Mathematical Induction to show that the following statement is true for all natural numbers [tex]\(n\)[/tex].

[tex]\[6 + 12 + 18 + \cdots + 6n = 3n(n+1)\][/tex]

1. Base Case:

Show that the first of these conditions is satisfied by evaluating the left and right sides of the given statement for the first natural number [tex]\(n = 1\)[/tex].

[tex]\[
\begin{aligned}
6 & = 3 \cdot 1 \cdot (1 + 1) \\
6 & = 6 \\
\end{aligned}
\][/tex]

2. Induction Hypothesis:

Assume that the statement is true for some natural number [tex]\(k\)[/tex], i.e.,

[tex]\[
6 + 12 + 18 + \cdots + 6k = 3k(k+1)
\][/tex]

3. Inductive Step:

To show that the statement is true for [tex]\(k + 1\)[/tex], write the given statement for [tex]\(k + 1\)[/tex]:

[tex]\[
6 + 12 + \cdots + 6k + 6(k+1) = 3(k+1)((k+1) + 1)
\][/tex]

Simplify the left side using the induction hypothesis:

[tex]\[
\begin{aligned}
3k(k+1) + 6(k+1) & = 3(k+1)(k+2)
\end{aligned}
\][/tex]

If the statement for [tex]\(k + 1\)[/tex] is true whenever the given statement [tex]\(6 + 12 + 18 + \cdots + 6n = 3n(n+1)\)[/tex] is true for all natural numbers.

4. Conclusion:

Using the statement for [tex]\(k\)[/tex]:

[tex]\[
6 + 12 + \cdots + 6k = 3k(k+1)
\][/tex]

To simplify the left side for [tex]\(k + 1\)[/tex]:

[tex]\[
\begin{aligned}
3k(k+1) + 6(k+1) &= 3(k+1)(k+2) \\
3(k+1)(k+1 + 1) &= 3(k+1)(k+2)
\end{aligned}
\][/tex]

Thus, by the principle of mathematical induction, the statement is true for all natural numbers [tex]\(n\)[/tex].


Sagot :

To use the Principle of Mathematical Induction to prove that the statement [tex]\( 6 + 12 + 18 + \cdots + 6n = 3n(n+1) \)[/tex] is true for all natural numbers [tex]\( n \)[/tex], we need to follow two steps:

1. Base Case: Verify the statement for [tex]\( n = 1 \)[/tex].
2. Induction Step: Assume the statement holds for some [tex]\( k \)[/tex] (induction hypothesis), and then prove it for [tex]\( k + 1 \)[/tex].

### Step 1: Base Case

Evaluate the left and right sides of the given statement for the first natural number [tex]\( n = 1 \)[/tex].

#### Left Side:
[tex]\[ 6 \cdot 1 = 6 \][/tex]

#### Right Side:
[tex]\[ 3 \cdot 1 \cdot (1 + 1) = 3 \cdot 1 \cdot 2 = 6 \][/tex]

Both sides are equal, so the base case holds:
[tex]\[ 6 = 6 \][/tex]

### Step 2: Induction Step

Assume the statement is true for [tex]\( n = k \)[/tex]. That is, we assume:
[tex]\[ 6 + 12 + 18 + \cdots + 6k = 3k(k+1) \][/tex]

We need to show that under this assumption, the statement is also true for [tex]\( n = k + 1 \)[/tex].

Write the given statement for [tex]\( n = k + 1 \)[/tex]:
[tex]\[ 6 + 12 + 18 + \cdots + 6k + 6(k+1) = 3(k+1)((k+1)+1) \][/tex]

Simplify the right side:
[tex]\[ 3(k+1)(k+2) \][/tex]

For the left side, use the induction hypothesis:
[tex]\( 6 + 12 + 18 + \cdots + 6k = 3k(k+1) \)[/tex].

So the left side for [tex]\( k + 1 \)[/tex] becomes:
[tex]\[ 3k(k+1) + 6(k+1) \][/tex]

Factor out [tex]\( 3(k+1) \)[/tex] from the terms on the left side:
[tex]\[ 3(k+1)k + 6(k+1) = 3(k+1)(k + 2) \][/tex]

Simplify:
[tex]\[ 3(k+1)(k + 2) \][/tex]

We see that the left side [tex]\( 3(k+1)(k + 2) \)[/tex] matches the simplified right side for [tex]\( k + 1 \)[/tex]:
[tex]\[ 3(k+1)(k+2) \][/tex]

Since both sides are equal, the induction step holds. Therefore, if the statement is true for [tex]\( n = k \)[/tex], it is also true for [tex]\( n = k + 1 \)[/tex].

### Conclusion

By the Principle of Mathematical Induction, since the statement is true for the base case ([tex]\( n = 1 \)[/tex]) and the induction step holds, the statement [tex]\( 6 + 12 + 18 + \cdots + 6n = 3n(n+1) \)[/tex] is true for all natural numbers [tex]\( n \)[/tex].